Coastal wetlands protection and development (World Bank, 1996)
The main objective of the preparation was to compose an environmentally-sound investment project for IDA financing for the coastal zone of the Minh Hai, Soc Trang and Tra Vinh province in the Mekong Delta, Vietnam.